Serbuk Gergaji Kayu Jati Teraktivasi EDTA Sebagai Penjerap Ion Tembaga (II) dan Krom (III) - Irdhawati, Irdhawati; Triyunita Sinthadevi, Ni Nyoman; Sahara, Emmy (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
Teak sawdust is a waste of the furniture industry. The main compound content is cellulose, which contains hydroxyl groups so that can be used as adsorbent. This work aims to determine adsorption capacity and isotherm adsorption pattern of teak sawdust activated by EDTA for copper (II) dan chromium (III) ions. Some parameters were optimized including the ratio of adsorbent and EDTA, and contact time. The results showed the optimum ratio of teak sawdust and EDTA was 2:3, and the optimum contact time was 105 minutes. Both of isoterm adsorption patterns of teak sawdust to Cu (II) and Cr (III) ions follow the Freundlich equation, with determination coefficient close to one. Optimum adsorption capacity was obtained 46.5 and 39.7 mg/g for Cu (II) and Cr (III), respectively.